Trends of leprosy and multibacillary infection in the state of Georgia since the early 1900s. - Carter D McCormick; Jacqueline Lea; Barbara M Stryjewska; Ashton Thompson; Jessica K Fairley (Public Library of Science (PLoS), 2019)
Few investigations to date have analyzed the epidemiology of Hansen's disease (leprosy) in the United States, and in particular, if birth location is related to multibacillary versus paucibacillary leprosy. We collected data on 123 patients diagnosed with leprosy in Georgia from the National Hansen's Disease Program from 1923-January 2018. A logistic regression model was built to examine the relationship between country of origin (U.S.-born or immigrant) and the type of leprosy. While the model showed no significant relationship between country of origin and type of leprosy, being Asian or Pacific Islander was associated with a higher odds of multibacillary disease (aOR = 5.71; 95% CI: 1.25-26.29). Furthermore, since the early 1900s, we found an increasing trend of leprosy reports in Georgia among both domestic born and immigrant residents, despite the overall decrease in cases in the United States during the same time period. More research is therefore necessary to further evaluate risk for multibacillary leprosy in certain populations and to create targeted interventions and prevention strategies.